A Review of the Feather Mite Genus Lopharalichus Gaud & Atyeo, 1996 (Acariformes: Pterolichidae), with Descriptions of Three New Species from Brazilian Parrots (Psittaciformes: Psittacidae) - Fabio Akashi Hernandes (Animals, 2023)
Feather mites of the genus Lopharalichus Gaud & Atyeo, 1996 (Pterolichidae: Pterolichinae), formerly containing three described species, are associated with New World parrots (Psittaciformes: Psittacidae) of the subfamily Arinae. Three new species of this genus are described: Lopharalichus tuimsp. nov. from Forpus xanthopterygius (Spix, 1824), L. spinosussp. nov. from Ara ararauna (Linnaeus, 1758), and L. chiririsp. nov. from Brotogeris chiriri (Vieillot, 1818). Type specimens of the previously described Lopharalichus species were examined, and a key to the known species is provided.